An assessment of the operationality and factors influencing the effectiveness of rabies surveillance in Gombe State, Nigeria. - Adebanwo Kuye; Mishel Dauda; Anthony Oche Ameh; Molta Idris Danladi; Yakubu Joel Atuman; Grace Sabo Nok Kia; Barbara Häsler (Public Library of Science (PLoS), 2024)
Rabies remains a burden in Africa, disproportionately affecting the most vulnerable despite the availability of effective vaccines. Nigeria, the most populous African country, needs rapid disease control actions and commitments to achieve the goal of eliminating dog-mediated rabies by 2030. Surveillance is an essential element of effective disease control strategies. This study examined the current state of operationality of the rabies surveillance system for early case detection and management in Gombe state, Nigeria, through a One Health lens. It further examined the barriers impeding the effectiveness of the surveillance based on the perception of surveillance workers. Qualitative and quantitative methods were used to assess the structure of the system and its functioning. Data on dog bite and rabid cases obtained from the veterinary services in Gombe state were analysed descriptively. A total of 13 key informants were interviewed using a semi-structured interview guide. Qualitative data were analysed using thematic analysis to explore in depth the factors that influenced the operationality of the system. A total of 157 potential human exposures to rabies were identified in this study, out of which two people reportedly died at the health facility after showing symptoms highly suggestive of rabies. In terms of rabies surveillance and control, cross-sectoral collaboration was found between the human health and veterinary sectors for risk assessment of potential rabies exposures and its management. Some identified factors affecting the operations of the surveillance were inadequate funding, lack of infrastructure, lack of feedback from higher authorities and insufficient knowledge of rabies prevention and management. To improve the capacity for case detection and management within the state, the appropriate authorities may focus on increasing awareness about the disease to the populace to increase the number of cases identified by the system, employ more workers and strengthen the surveillance capability of existing workers.